Edukacja domowa – kilka uwag w kontekście dyskursu o edukacji demokratycznej - Helios, Joanna (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2014)
The article presents home teaching in the context of the discourse on democratic education. The author discusses two problems: first, the role of home schooling in the context of compulsory schooling and the right to education; secondly, the legal aspects of home schooling.
Homeschooling – a few remarks in the context of the discourse on democratic education
Keywords: homeschooling; freedom; the right to education; compulsory schooling; democratic education